Women Empowerment from the Perspective of their Presence in Leadership Roles in Nepalese Commercial Bank - Shrestha, Neha (Nepalese Journal of Business, 2025)
This study examines the Women empowerment from the perspective of their presence in leadership roles Nepalese commercial banks. Bank performance is the dependable variables. The independent variables are freedom, education, motivation, need for achievement, self-confidence. The study is based on primary data with 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the women empowerment and bank performance in Nepalese commercial banks. The study showed that self-confidence has a positive impact on bank performance. It indicates that increase in self-confidence leads to increase on bank performance. Likewise, education has a positive impact on bank performance. It indicates that higher the education, better would be the bank performance. Similarly, motivation has a positive impact on bank performance. It implies that higher the motivation, better will be the bank performance. Moreover, need for achievement has a positive impact on bank performance. It indicates that higher the need for achievement, better would be the bank performance. Likewise, freedom has a positive impact on bank performance. It indicates that increase in freedom leads to increase in bank performance.